Occupation and education in relation to risk factors of ischaemic heart disease in the male industrial population - Simon, J; Cajzl, L; Krizanovská, M; Krízek, M; Kraus, J (Cor et vasa, 1986)
In a sample of 3,757 men aged 40-50 years, all employees of a large industrial plant, the authors studied the prevalence of several risk factors (RF) of ischaemic heart disease (IHD) in relationship to profession and education of probands. Blue collar workers were more frequently heavy smokers and regular alcohol consumers than white collars. Compared with other workmen professions a tendency towards a higher risk profile was present in employees doing strenuous manual work. These were heavier smokers, had higher blood pressure and serum cholesterol. Within white-collar professions a higher risk profile was observed in managers with high responsibility than in personnel of the research and development departments. The former were heavier smokers, had higher serum cholesterol and greater overweight. The education level was in indirect association with smoking, hypertension and obesity but correlated directly with regular alcohol consumption. Socio-economic factors evidently influence the prevalence of risk factors of IHD also in the Czech industrial population.
Keywords: Socioeconomic Factors; Cross-Sectional Studies; Male; Middle Aged; Coronary Disease; výchova a vzdělávání; Obesity; průmysl; koronární nemoc; Cholesterol; obezita; Adult; socioekonomické faktory; dospělí; mužské pohlaví; Smoking; cholesterol; lidé; Humans; průřezové studie; Risk; pití alkoholu; Alcohol Drinking; Occupations; zaměstnání; Education; riziko; lidé středního věku; kouření; Industry